Tracking nitroxyl-derived posttranslational modifications of phospholamban in cardiac myocytes - Mundiña, Cecilia Beatriz (2019)
Cardiovascular disease is the leading cause of morbidity and mortality worldwide. Calcium (Ca2+) mishandling is one of the most striking abnormalities in this wide spectrum of pathologies, among which heart failure (HF) remains the leading cause of death in developed countries (Benjamin et al., 2018). A hallmark of HF in both human and animal models is impaired Ca2+ sequestration into the SR, which contributes to the decreased contractile performance in this disease (Gwathmey et al., 1987; Meyer et al., 1995; del Monte et al., 2002). Not surprisingly, this defective mechanism has been targeted with novel therapeutic strategies that are now undergoing experimental and clinical testing in animals and patients (Pfeffer et al., 2015; Hulot et al., 2016, 2017; Motloch et al., 2018). In this issue of JGP, Keceli et al. provide novel insights into the molecular mechanism from which nitroxyl (HNO), nitric oxide (NO)´s one-electron-reduced and protonated sibling, recently emerged as a promising candidate for HF treatment.